The effects of complications, frequency of control and education level on quality of life of type 2 diabetes mellitus patients - Nasriyah, Chotijatun; Marselin, Amanda (International Journal Of Community Medicine And Public Health, 2021)
Background: Diabetes mellitus (DM) is a chronic disease with multiple aetiologies characterized by an increase in blood glucose levels exceeding normal limits. The world health organization predicts an increase in people with DM2 in Indonesia from 8.4 million to 21.3 million in 2030. Diabetes mellitus is one of the ninth main causes of decreased life expectancy, so it will greatly affect the quality of life of a person suffering from DM. Several factors that affect the quality of life of DM patients include age, gender, length of suffering, complications, education, marital status, level of compliance and occupation. Methods: This type of research is descriptive research with total sampling and obtained a sample of 26 respondents. Measurement of quality of life using the SF-36 instrument then the results were analysed using the chi square test to see the relationship between the factors that affect the quality of life. Results: The results obtained statistically that the complication factor (p=0.189) and the control frequency factor (p=0.596) did not significantly affect the quality of life. While the level of education statistically (p=0.006) affects the quality of life of DM patients. Conclusions: The results of the statistical study between complication factors and the frequency of control on the quality of life of DM patients showed no significant relationship. Meanwhile, the education level factor, both statistically and clinically, showed that there was a significant relationship with the quality of life of DM patients.